2022
DOI: 10.1093/cercor/bhac061
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory cortex of macaque monkeys is designed for opposable thumb

Abstract: The evolution of opposable thumb has enabled fine grasping ability and precision grip, therefore the ability to finely manipulate the objects and refined tool use. Since tactile inputs to an opposable thumb are often spatially and temporally out of sync with inputs from the fingers, we hypothesized that inputs from the opposable thumb would be processed in an independent module in the primary somatosensory cortex (area 3b). Here we show that in area 3b of macaque monkeys, most neurons in the thumb representati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Most neurons in the BA 3b thumb representation specifically respond to tactile stimulation of the thumb but not to tactile stimulation of other fingers and interconnect only sparsely to other digit representations. Also in macaque monkeys, the thumb representation may act as an independent module processing selective information, whereas information content is more distributed between other fingers ( Lazar et al, 2022 ). This may be linked to its special role for tool use.…”
Section: Discussionmentioning
confidence: 99%
“…Most neurons in the BA 3b thumb representation specifically respond to tactile stimulation of the thumb but not to tactile stimulation of other fingers and interconnect only sparsely to other digit representations. Also in macaque monkeys, the thumb representation may act as an independent module processing selective information, whereas information content is more distributed between other fingers ( Lazar et al, 2022 ). This may be linked to its special role for tool use.…”
Section: Discussionmentioning
confidence: 99%
“…Most neurons in the BA 3b thumb representation specifically respond to tactile stimulation of the thumb, but not to tactile stimulation of other fingers, and interconnect only sparsely to other digit representations. Also in macaque monkeys, the thumb representation may act as an independent module processing selective information, whereas information content is more distributed between other fingers (Lazar et al, 2023). This may be linked to its special role for tool use.…”
Section: Discussionmentioning
confidence: 99%
“…Also in macaque monkeys, the thumb representation may act as an independent module processing selective information, whereas information content is more distributed between other fingers (Lazar et al, 2023). This may be linked to its special role for tool use.…”
Section: Topographic 3d Structural Architecture Of Ba 3b Hand and Fac...mentioning
confidence: 99%
“…A possible explanation for this finding comes from a recent study that observed within area 3b of S1 a homogeneous 3D structural architecture between digits 2-5, excluding the thumb (Doehler et al, 2023). Greater independence of the thumb has also been observed within area 3b of macaque monkeys (Lazar et al, 2023). It is unlikely that this independence holds for area 1, where integration across fingers is known to occur.…”
Section: Rubber Hand Illusion Strength Is Associated With Attenuated ...mentioning
confidence: 96%